Pengaruh stunting terhadap perkembangan kognitif pada balita hingga remaja - Natassya, Priska; Soesanto, Sheila (Fakultas Kedokteran Gigi Universitas Trisakti, 2024)
The first five years of childhood are a period or stage of age that determines human quality in adulthood. The critical period of children up to the age of the first two years is a period called the window of opportunity that requires nutritional support, special stimulus, and intervention. The Problem of Lack of Protein Energy (KEP) is one of the main nutritional problems that occur in toddlers and is very influential on the child's growth process. To find out if toddlers are stunted, the World Health Organization (WHO) used the growth standard as a reference by measuring the value of Z (Z score). There are 3 indicators, namely weight for length (WLZ), length for age (LAZ), and weight for age (WAZ). If the child is stunted, then the Z Standard Deviation (SD) score in the LAZ score is less than -2. To measure motoric capability, MSEL: AGS (Mullen Scales of Early Learning: AGD Edition) can be used. This method is used to measure cognition in children by measuring 5 cognitive scales i.e. Gross motor (GM), fine motor, visual capture, receptive language, and expressive language. This stunting condition can affect the cognitive development and brain growth of the child. Cognitive decline can lead to a lack of productivity and can decrease the learning achievement of children, even to adolescence